Local Bismuth Thiols Potentiate Antibiotics and Reduce Infection in a Contaminated Open Fracture Model. Issue 2 (February 2015) - Penn-Barwell, Jowan G.; Baker, Brett; Wenke, Joseph C.
Abstract : Objective: This proof-of-concept study tested the hypothesis that combining bismuth thiols (BTs) with systemic antibiotics will more effectively reduce infection in an animal model of contaminated open fracture than systemic antibiotics alone. Methods: An implant-stabilized segmental defect rat model was contaminated with Staphylococcus aureus and then treated with surgical debridement 6 hours after injury and 3 days of systemic cefazolin. A single dose of BTs suspended in a hydrogel was administered to the wound immediately after debridement. After 14 days, the bone and implant were harvested for microbiological analysis. Results: A single local dose of 0.05 mg of BT (MB-8-2), when combined with systemically administered cefazolin, decreased infection, without any noticeable local or systemic toxicity, from 60% to 10% ( P = 0.002), with only 0.02% of the recovered bacteria quantity of the cefazolin-only group ( P < 0.001). Higher doses were less effective and caused side-effects. Conclusions: BTs administered locally to infected open fracture wounds at an appropriate dose potentiate the effect of systemically administered antibiotics and reduce infection rate and bacteria quantity associated with bone and orthopaedic implants. Local delivery of BTs is a promising strategy for increasing the efficacy of systemically administered antibiotics in preventing and treating infections of open fractures.